SDG14 assessment of progress against sustaining life below water: a case study from Torres Strait - Éva Plagányi; Nicole Murphy; Roy Aijun Deng; Laura K. Blamey; Stephanie Brodie; Leo X. C. Dutra; Steven Edgar; Denham Parker; Kinam Salee; Mark Tonks; Sharon A. Appleyard (Reviews in Fish Biology and Fisheries, 2026)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

A Circular RNA Expressed from the FAT3 Locus Regulates Neural Development - Sabine Seeler; Maria Schertz Andersen; Tamas Sztanka-Toth; Mateja Rybiczka-Tešulov; Marleen H. van den Munkhof; Chi-Chih Chang; Muyesier Maimaitili; Morten Trillingsgaard Venø; Thomas Birkballe Hansen; R. Jeroen Pasterkamp; Agnieszka Rybak-Wolf; Mark Denham; et al. (Molecular Neurobiology, 2023)
Circular RNAs (circRNAs) are key regulators of cellular processes, are abundant in the nervous system, and have putative regulatory roles during neural differentiation. However, the knowledge about circRNA functions in brain development is limited. Here, using RNA-sequencing, we show that circRNA levels increased substantially over the course of differentiation of human embryonic stem cells into rostral and caudal neural progenitor cells (NPCs), including three of the most abundant circRNAs, ciRS-7, circRMST, and circFAT3. Knockdown of circFAT3 during early neural differentiation resulted in minor transcriptional alterations in bulk RNA analysis. However, single-cell transcriptomics of 30 and 90 days differentiated cerebral organoids deficient in circFAT3 showed a loss of telencephalic radial glial cells and mature cortical neurons, respectively. Furthermore, non-telencephalic NPCs in cerebral organoids showed changes in the expression of genes involved in neural differentiation and migration, including FAT4 , ERBB4 , UNC5C , and DCC . In vivo depletion of circFat3 in mouse prefrontal cortex using in utero electroporation led to alterations in the positioning of the electroporated cells within the neocortex. Overall, these findings suggest a conserved role for circFAT3 in neural development involving the formation of anterior cell types, neuronal differentiation, or migration.

Directly Reprogrammed Neurons Express MAPT and APP Splice Variants Pertinent to Ageing and Neurodegeneration - Mette Habekost; Per Qvist; Mark Denham; Ida E. Holm; Arne Lund Jørgensen (Molecular Neurobiology, 2021)
Neurons produced by reprogramming of other cell types are used to study cellular mechanisms of age-related neurodegenerative diseases. To model Alzheimer’s disease and other tauopathies, it is essential that alternative splicing of the MAPT transcript in these neurons produces the relevant tau isoforms. Human neurons derived from induced pluripotent stem cells, however, express tau isoform compositions characteristic of foetal neurons rather than of adult neurons unless cultured in vitro for extended time periods. In this study, we characterised the dynamics of the MAPT and APP alternative splicing during a developmental time-course of porcine and murine cerebral cortices. We found age-dependent and species-specific isoform composition of MAPT , including 3R and 4R isoforms in the porcine adult brain similar to that of the adult human brain. We converted adult and embryonic fibroblasts directly into induced neurons and found similar developmental patterns of isoform composition, notably, the 3R and 4R isoforms relevant to the pathogenesis of Alzheimer’s disease. Also, we observed cell-type-specific isoform expression of APP transcripts during the conversion. The approach was further used to generate induced neurons from transgenic pigs carrying Alzheimer’s disease-causing mutations. We show that such neurons authentically model the first crucial steps in AD pathogenesis.

Improving Long-term Monitoring of Contaminated Groundwater at Sites where Attenuation-based Remedies are Deployed - Miles E. Denham; Mark B. Amidon; Haruko M. Wainwright; Baptiste Dafflon; Jonathan Ajo-Franklin; Carol A. Eddy-Dilek (Environmental Management, 2020)

Fire severity drives variation in post-fire recruitment and residual seed bank size of Acacia species - Harrison D. Palmer; Andrew J. Denham; Mark K. J. Ooi (Plant Ecology, 2018)

Projected soil temperature increase and seed dormancy response along an altitudinal gradient: implications for seed bank persistence under climate change - Mark K. J. Ooi; Tony D. Auld; Andrew J. Denham (Plant and Soil, 2012)

Disruption of recruitment in two endemic palms on Lord Howe Island by invasive rats - Tony D. Auld; Ian Hutton; Mark K. J. Ooi; Andrew J. Denham (Biological Invasions, 2010)

Climate change and bet‐hedging: interactions between increased soil temperatures and seed bank persistence - MARK K. J. OOI; TONY D. AULD; ANDREW J. DENHAM (Global Change Biology, 2009)
In order to predict the long‐term consequences of climate change, it is necessary to link future environmental changes to mechanisms that control plant population processes. This information can then be incorporated into strategies to more accurately model climate change impacts on species or to estimate future extinction risks. We examined the impact of increased temperatures on the longevity and dynamics of the persistent soil seed banks of eight ephemeral species from arid Australia. We found that the predicted global temperature increases under climate change will be reflected in increased soil temperatures, and that seeds in the soil seed bank will be exposed to long durations of high temperatures over the summer months. Three of the eight species studied had significantly greater levels of germination after exposure to predicted increased soil temperatures. Another species displayed a dramatic decrease in seed viability after such exposure. The capacity of such species to use the seed bank to bet hedge against rainfall events that cause germination but are insufficient to allow plant maturation, is compromised by increased germinability and subsequent loss or reduction of seed bank persistence. These predicted changes in the dynamics of soil seed banks increase the risk of local extinctions of these species, while the composition of the community may be altered by changes in species abundance. Our results show that the risk spreading mechanism provided by persistent seed banks could be compromised by the mechanistic impact of forecast temperature increases in arid habitats, and highlight the need to understand mechanisms that control population dynamics when attempting to address likely future impacts of climate change on biodiversity.